Reasons for low long-lasting insecticide-treated net use and repurposing: qualitative study from southern Ethiopia - Endriyas, Misganu; Kassa, Mekidm; Melka, Mintesinot; Gebru, Agegnehu; Chisha, Yilma (Frontiers in Public Health, 2025)
BackgroundLong-lasting insecticidal nets (LLINs) are the main vector control tools and remain protective against malaria, even in the presence of high pyrethroid resistance. However, in sub-Saharan Africa, the estimated percentage of the population sleeping under LLINs is low. Hence, this qualitative study was conducted to explore perceptions about LLINs and the reasons for low LLIN use in southern Ethiopia.MethodsQualitative cross-sectional study was conducted in southern Ethiopia. Study areas were selected based on low LLIN use following a quantitative survey. Seven focus group discussions (FGDs) with a total of 52 discussants were conducted. Data were managed manually using Microsoft Word and were analyzed thematically.ResultsThe themes that emerged were ownership of LLINs, perceived lifespan of LLINs, uses of LLINs, reasons for LLIN non-use, and recommendations. Participants indicated low LLIN coverage and interrupted maintenance supply. The pattern of LLIN utilization varied between groups, as some said it was improving while others said it was decreasing. The expected life span of LLINs reported varied from a minimum of 3 months to a maximum of 3 years. Discussants from all FGDs described that the possibility of discarding or repurposing LLINs is high when it does not kill mosquitoes. Some discussants added the finding that ineffectiveness was worsened by exposing LLINs to direct sunlight to decrease suffocation. All FGD discussants agreed that the main reason for not using LLINs was a lack of awareness, which in turn caused negligence. Some groups in pastoralist areas added the perception that LLINs do not protect from malaria as a reason for non-use.ConclusionThe low LLIN use and high repurposing practices were noted due to different reasons, including low awareness, negligence, ineffectiveness of LLINs in killing mosquitoes, and others. LLINs are repurposed mainly for covering different things and making ties. Continuous awareness creation activities and corrective measures might improve LLIN coverage and use.